Inhibition of Dorsal Root Ganglia Transient Receptor Potential Ankyrin 1 Upregulation Contributes to the Protective Effect of Morphine Against Gastric Mucosal Damage Induced by Water-Immersion Restraint Stress - Jiang, Qun; Jiang, Peng; Guo, Mingyan; Xie, Chuangbo; Ling, Qiong; Zhao, Gaofeng; Tu, Weifeng; Li, Xiangyu (Turkish Journal of Gastroenterology, 2024)
Background/Aims: The pathogenesis mechanism of acute gastric mucosal lesions (AGML) is still unclear; further exploration is urgently needed to find a new therapeutic target. This study aimed to investigate whether morphine might regulate the expression and function of transient receptor potential ankyrin 1 (TRPA1) through a cyclic adenosine monophosphate/protein kinase A (cAMP/PKA)-dependent pathway, thereby alleviating gastric mucosal lesions caused by water-immersion restraint stress (WIRS). Materials and Methods: Rats were administered with intrathecal morphine, TRPA1 antagonist (HC-030031), µ-opioid receptor antagonist, or protein kinase A inhibitor (H-89), respectively, before WIRS. After 6 hours of WIRS, microscopic lesions, hematoxylin and eosin staining, and transmission electron microscopy were applied to assess the damage of the gastric mucosa. Real-time polymerase chain reaction, Western blot, and enzyme-linked immunosorbent assay were conducted to detect the levels of TRPA1 and substance P (SP) in the dorsal root ganglia (DRG) and gastric tissues. In addition, immunofluorescence was used to explore the possible co-expression of TRPA1 and µ-opioid receptors in the DRG. Results: The results indicated that WIRS upregulated TRPA1 and SP in gastric mucosa, and HC-030031 or H-89 could alleviate gastric mucosal lesions caused by WIRS (P < .0001). Morphine was found to suppress both WIRS-induced gastric mucosal lesions (P < .0001) and the upregulation of TRPA1 (P = .0086) and SP (P = .0013). Conclusion: Both TRPA1 and SP play important roles in the pathogenesis of WIRS-induced AGML. Exogenous gastroprotective strategies reduce elevated levels of TRPA1 via the cAMP/PKA-dependent pathway. Inhibition of TRPA1 upregulation in the DRG is critical for intrathecal morphine preconditioning-induced gastric protection. Cite this article as: Jiang Q, Jiang P, Guo M, et al. Inhibition of dorsal root ganglia transient receptor protein ankyrin 1 upregulation contributes to the protective effect of morphine against gastric mucosal damage induced by water-immersion restraint stress. Turk J Gastroenterol. 2024;35(6):453-464.